National Integration Education Practices In Post-Conflict Regions - Rahman, Aulia; Abdurrahman Usman, Zulkifli; Anis, Madhan; Prasetyo, Okhaifi; Sugiantoro; Riyani, Mufti; Rosyid MA, Ikhsan (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
This study examines the practice of national integration education in post-conflict Aceh, focusing on the materials, approaches, and challenges faced in its implementation. The Aceh conflict (1975–2004) left deep social, economic, and psychological scars, necessitating educational interventions to foster unity and prevent disintegration. National integration education aims to cultivate values of tolerance, solidarity, and social justice among students, aligning with multicultural and peace education principles while emphasizing national cohesion. Using qualitative methods, including interviews and observations with selected teachers and students, this research explores how national integration education is taught in schools. Findings indicate that while the program has successfully raised students' conflict sensitivity and reinforced peace-building values, challenges remain in pedagogical approaches and institutional support. The study highlights the importance of experiential and contextually relevant learning both inside and outside the classroom to strengthen national integration. The study contributes to the discourse on post-conflict education by advocating for a more structured and inclusive approach to national integration education, ensuring it addresses historical divisions and promotes lasting social harmony.